Profiling Auspicious Butyrylcholinesterase Inhibitory Activity of Two Herbal Molecules: Hyperforin and Hyuganin C - Orhan, Ilkay Erdogan; Senol Deniz, F. Sezer; Trædal‐Henden, Steinar; Cerón‐Carrasco, José P.; den Haan, Helena; Peña‐García, Jorge; Pérez‐Sánchez, Horacio; Emerce, Esra; Skalicka‐Wozniak, Krystyna (Chemistry & biodiversity, 2019)
Cholinergic therapy based on cholinesterase (ChE) inhibitory drugs is the mainstay for the treatment of Alzheimer's disease. Therefore, an extensive research has been continuing for the discovery of drug candidates as inhibitors of acetyl‐ and butyrylcholinesterase. In this study, two natural molecules, e. g. hyperforin and hyuganin C were tested in vitro for their AChE and BChE inhibitory activity. Both of the compounds were ineffective against AChE, whereas hyperforin (IC50=141.60±3.39 μm) and hyuganin C (IC50=38.86±1.69 μm) were found to be the highly active inhibitors of BChE as compared to galantamine (IC50=46.58±0.91 μm) which was used as the reference. Then, these molecules were further proceeded to molecular docking experiments in order to establish their interactions at the active site of BChE. The molecular docking results indicated that both of them are able to block the access to key residues in the catalytic triad of the enzyme, while they complement some of the hydrophobic residues of the cavity, what is consistent with our in vitro data. While both compounds were predicted as mutagenic, only hyuganin C showed hepatotoxicity in in silico analysis. According to whole outcomes that we obtained, particularly hyuganin C besides hyperforin are the promising BChE inhibitors, which can be the promising compounds for AD therapy.